2017
DOI: 10.1007/s00066-017-1163-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a rectal and bladder preparation protocol on prostate cancer outcome in patients treated with external beam radiotherapy

Abstract: We found strong evidence that rectal and bladder preparation significantly decreases biochemical and clinical failures and the probability of death from PCa in patients treated without daily image-guided prostate localization, presumably since patients with RBP are able to maintain a reproducibly empty rectum and comfortably full bladder across the whole treatment compared with NRPB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Prostate radiotherapy accuracy is impacted by the uncertainties of proximal organs at risk (OARs) such as the filling rate and volumes of the bladder and rectum [1,2]. Since 2014, majority of prostate patients at our centre have been treated using Volumetric Arc Therapy (VMAT) to reduce treatment time and thus intrafraction motion.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate radiotherapy accuracy is impacted by the uncertainties of proximal organs at risk (OARs) such as the filling rate and volumes of the bladder and rectum [1,2]. Since 2014, majority of prostate patients at our centre have been treated using Volumetric Arc Therapy (VMAT) to reduce treatment time and thus intrafraction motion.…”
Section: Introductionmentioning
confidence: 99%
“…Although modern localization modalities have significant advantages, they should not be relied upon to overcome poor simulation technique as the goal of simulation is to replicate the conditions that will be used during therapy. For example, significant rectal distension on the initial planning CT is often a compelling indication of prostate deformation and rotation about its typical configuration, and effort should be made to minimize rectal distention ( 44 ). The various IGRT methods are reviewed in more detail below.…”
Section: Techniquesmentioning
confidence: 99%
“…3 In radiation therapy, it is important to perform a secure delivery of high doses with dose minimization to adjacent organs at risk. 4,5 The accuracy of any radiation therapy is however limited by several factors, including set-up error, organ delineation, inter-and intra-fraction organ translocation, and target organ distortion. 6 Rectal distension and, to a lesser extent, bladder filling have been found to be the principal causes of prostate translocation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Rectal distension and, to a lesser extent, bladder filling have been found to be the principal causes of prostate translocation. 4,[7][8][9] Despite this, there is a lack of consensus regarding the optimal degree of bladder filling during radiation therapy, with recommendations encompassing a spectrum of an empty, partially full, comfortably full or full bladder. 4,8,[10][11][12][13] Some studies have shown that radiation therapy with a full bladder protocol has distinct advantages in relation to dose load to both rectum and bladder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation